Symbolic Consumption in the Indian Markets: Analysis of Determining Factors - Suma, Vadrevu Pragnya (Archives of Business Research, 2018)
Researchers have tried hard to understand the concept of symbolic consumption and more precisely the reasons for symbolic consumption as it is one of the central issues of concern around which the marketing strategy for many products revolves. There are many products being purchased for the symbolic value they carry, rather than the functional value or the utilitarian value of the product. Researchers classified the needs into functional, emotional and symbolic needs. While the lesser known and understood facts about symbolic consumption and the changing behaviour of consumers are being worked upon by various researches, the constant change in the pattern of this behaviour makes it difficult for researchers to stick to a particular stream and area of research. The term symbolic consumption is used to describe the phenomenon whereby people consume to reflect their sense of self-identity. Symbolic consumption has been addressed primarily not only in consumer studies, but also in anthropology, sociology, economics, marketing, human ecology, and social psychology. Over the period, consumers have constantly changed their perceptions and notions regarding branded products and their value. The driving factors that make the consumer consume or not a particular product are varied and influence the process in various possible combinations of these individual factors. Questions regarding why a product is purchased by a group of people, the recurrence of its purchase or why a product is selected over the others have always been revolving in the minds of marketing groups and researchers. This paper analyses the theoretical aspects of the determinants of the constantly varying consumer behaviour in indulging in symbolic consumption of brands in the Indian scenario with a focus on the determinants which affect the consumer in their buying decision are examined.